Impact of the nanoparticle-protein corona on colloidal stability and protein structure - Peukert, Wolfgang; Gebauer, Julia; Malissek, Marcelina; Simon, Sonja; Knauer, Shirley; Maskos, Michael; Stauber, Roland; Treuel, Lennart (Langmuir, 2012)
In biological fluids, proteins may associate with nanoparticles (NPs), leading to the formation of a so-called "protein corona" largely defining the biological identity of the particle. Here, we present a novel approach to assess apparent binding affinities for the adsorption/desorption of proteins to silver NPs based on the impact of the corona formation on the agglomeration kinetics of the colloid. Affinities derived from circular dichroism measurements complement these results, simultaneously elucidating structural changes in the adsorbed protein. Employing human serum albumin as a model, apparent affinities in the nanomolar regime resulted from both approaches. Collectively, our findings now allow discrimination between the formation of protein mono- and multilayers on NP surfaces. © 2012 American Chemical Society.
Keywords: fluid; protein; nanoparticle; protein; corona; agglomeration; multilayer